Perfil antropometrico, somatotipo y composicion corporal de jovenes piragüistas - Carrasco Paez, L.; Martinez Pardo, E.; Nadal Soler, C. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2005)
The aim of this study was to define the anthropometric profile and several parameters related to their body composition. A group of 69 paddlers (48 males and 21 females), 13 and 14 years old, were evaluated taken into account variables such as gender and paddling practice (canoe or kayak). Body fat parameters were significantly higher in female paddlers, although weight, height, bone mass, muscular mass, mesomorphy, and diameters measured (styloid process, humerus epicondyle, and femoral epicondyle) were higher in males. Gender differences were confirmed after somatotype comparison where a SDD of 3.31 was registered. According to the paddlers` speciality and attending to the male gender exclusively, height, weight, and diameters measured were significantly higher in kayak paddlers. Correlation analysis showed a strong relationship between fat mass and sums of four and six skinfolds. Also, a significant correlation between endomorphy and those parameters related to body fat was observed.